Effect of the Duration of Deep Hypothermic Circulatory Arrest on the Neurodevelopmental Outcomes in Children Undergoing Cardiac Surgery - Abdullah H. Ghunaim; Basma Aljabri; Ahmed Dohain; Ghassan S. Althinayyan; Abdulaziz I. Aleissa; Ahmad T. Alshebly; Rayan A. Alyafi; Tareg M. Alhablany; Ahmed M. Nashar; Osman O. Al-Radi (MDPI AG, 2024)
Background/Objectives: Deep hypothermic circulatory arrest (DHCA) is safe, but subtle neurodevelopmental deficits may persist far beyond the perioperative period. We aimed to investigate the relationship between DHCA duration and neurodevelopmental outcomes in young children undergoing cardiac surgery with DHCA. Methods: Children aged < 42 months, including neonates who underwent cardiac surgery using DHCA without regional perfusion techniques, were included as the DHCA group. Children in the same age range who underwent cardiac surgery without DHCA were included as the control group. All enrolled patients underwent neurodevelopmental assessment using the Bayley Scales of Infant and Toddler Development (BSTID) by a trained pediatrician, and 17 DHCA patients and 6 control patients completed the BSTID assessment. Results: Both groups showed no significant preoperative, operative, or postoperative differences. Adjusted multivariable analysis revealed that prematurity and age at assessment were significant changing predictors of each of the BSTID components (p < 0.001), except for the gross motor component, where only age at assessment was a significant adjusting predictor. Longer DHCA was associated with lower fine and gross motor BSTID components; however, the association was not statistically significant (p = 0.06). Conclusions: Long-duration DHCA without regional perfusion techniques may be associated with less optimal neurodevelopmental outcomes.